A comparison between fentanyl and esmolol in preventing increase intracranial pressure during endotracheal suction in severe head injury patient - Muhammad, Hasmizy (2006)
Background Preventing increases m intracranial pressure while maintaining adequate cerebral perfusion is a primary goal in the treatment of adults with a severe head injury. Routine nursing interventions can trigger reactive intracranial hypertension. For example, endotracheal suctioning causes a progressive increase in intracranial pressure with each insertion of the suctioning catheter. In current practice fentanyl, a rapid onset opiod was given before suctioning to blunt responses to noxious stimuli. Esmolol, a rapid- onset and short-acting selective betal-adrenergic receptor antagonist is utilized to attenuate the cardiovascular response to laryngoscopy and as an adjWlct to controlled circulatory techniques. Objectives The goals of this study are to observe the effect of fentanyl and esmolol on the changes in intracranial pressure, cerebral perfusion pressure, mean arterial pressure and heart rate responses during endotracheal suctioning in adults with severe head injuries and to compare the effect of fentanyl and esmolol in preventing increase in intracranial pressure during endotracheal suction. Methods Sixty two patients who are admitted to neurointensive care unit with Glasgow Coma Scale (GCS) of 8 and less, with intracranial pressure monitoring in place and mechanically ventilated. The patients were then randomly received either esmolol (lmglkg) or fentanyl (lmcglkg) before endotracheal suction. Arterial blood pressure (ABP), mean arterial pressure (MAP)~ heart rate (HR), intracranial pressure (ICP)~ cerebral perfusion pressure (CPP)~ arterial blood gases (ABG) and bispectral index (BIS) were recorded at baseline, immediately after and 5 minutes, 10 minutes and 15 minutes after endotracheal suctioning. Results There were no significant difference in ICP and BIS in patients who are given either fentanyl or esmolol in preventing a raise in intracranial pressure during endotracheal suctioning. A significant difference was seen in mean arterial pressure, cerebral perfusion pressure and heart rate. Conclusion We conclude that in patients with severe head injury who are well sedated and had a normal intracranial pressure, the used of fentanyl or esmolol in preventing a raise in intracranial pressure during endotracheal suction has no advantage. However, esmolol (1 mglkg) is better than fentanyl ( 1 meg/kg) in control mean arterial pressure and cerebral perfusion pressure during endotracheal suctioning.